2015
DOI: 10.1039/c5tc00727e
|View full text |Cite
|
Sign up to set email alerts
|

Red emissive organic light-emitting diodes based on codeposited inexpensive CuI complexes

Abstract: Red emissive CuI complexes and their organic light-emitting diodes were prepared by codeposition of CuI and isoquinoline based ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…These two kinds of hybrid materials have obvious differences in luminescence, stability and other properties, due to their differences in structural types and coordination [10] . Copper(I) halide hybrid luminescent materials have many advantages such as structure diversity, facile synthesis, high luminescent efficiency and tunable optical performance, exhibiting great promise in solid‐state‐lightings and displays [9b,15] . However, compared with the properties of commercial rare‐earth metal based phosphors, the reported compounds typically have poor stability, complicated synthetic procedures, low luminescent efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…These two kinds of hybrid materials have obvious differences in luminescence, stability and other properties, due to their differences in structural types and coordination [10] . Copper(I) halide hybrid luminescent materials have many advantages such as structure diversity, facile synthesis, high luminescent efficiency and tunable optical performance, exhibiting great promise in solid‐state‐lightings and displays [9b,15] . However, compared with the properties of commercial rare‐earth metal based phosphors, the reported compounds typically have poor stability, complicated synthetic procedures, low luminescent efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Organic light-emitting devices (OLEDs) have been attracting great interest for their applications in flat panel displays and solid-state lighting. A lot of work on material research and device engineering has been reported both in fluorescent devices and phosphorescent devices. Blue emitters, one of the key components for a full-color display, can also serve as hosts for lower energy dopant emitters by energy transfer to generate emission of other colors due to their intrinsic large energy gaps. , However, stable blue-emitting materials and devices still need to be explored as compared to the red or green ones. Among the efforts to achieve excellent blue-emitting materials, designing bipolar molecules with donor and acceptor motifs seems to be an effective way because such materials can usually exhibit good electron mobility as well as hole mobility, thus leading to the simplification of device fabrication by replacing complicated multilayer devices with comparatively simple devices. , …”
Section: Introductionmentioning
confidence: 99%